On 2-Absorbing Quasi-Primary Ideals in Commutative Rings - KOÇ, SUAT; TEKİR, ÜNSAL (SPRINGER HEIDELBERG, 2016)
Let R be a commutative ring with nonzero identity. In this article, we introduce the notion of 2-absorbing quasi-primary ideal which is a generalization of quasi-primary ideal. We define a proper ideal I of R to be 2-absorbing quasi primary if root I is a 2-absorbing ideal of R. A number of results concerning 2-absorbing quasiprimary ideals and examples of 2-absorbing quasi-primary ideals are given.
Keywords: Prime ideal; 2-Absorbingideal; 2-Absorbing quasi-primaryideal